Software Process Dynamics and Agility International Conference on Software Process, ICSP 2007, Minneapolis, MN, USA, May 19-20, 2007, Proceedings - Wang, Qing; Pfahl, Dietmar; Raffo, David M. (Programming and Software Engineering, 2007)
This volume contains papers presented at the International Conference on Software Process (ICSP 2007) held in Minneapolis, USA, May 19-20, 2007. ICSP 2007 c- prised two successful series of process-related workshops, the International Workshop on Software Process Simulation and Modeling (ProSim) and the Software Process Workshop (SPW). The theme of ICSP 2007 was "Coping with Software Process Dynamics and Ag- ity. " Software developers work in a dynamic context of frequently changing te- nologies and limited resources. Globally distributed development teams are under ever-increasing pressure to deliver their products more quickly and with higher levels of quality. At the same time, global competition is forcing software development organizations to cut costs by rationalizing processes, outsourcing part or all of their activities, reusing existing software in new or modified applications and evolving existing systems to meet new needs, while still minimizing the risk of projects failing to deliver. To address these difficulties, new or modified processes are emerging, including agile methods and plan-based product line development. Open source, COTS and community-developed software are becoming more popular. Outsourcing coupled with 24/7 development demand well-defined processes to support the - ordination of organizationally and geographically separated teams. The increasing challenges faced by the software industry combine to increase - mands on software processes. ICSP 2007 was a continuation of two successful series of process-related wo- shops, ProSim (Software Process Simulation and Modeling Workshop) and SPW (Software Process Workshop).